Electrophysiological Response to the Informative Value of Feedback Revealed in a Segmented Wisconsin Card Sorting Test - Li, Fuhong; Wang, Jing; Du, Bin; Cao, Bihua (Frontiers in Psychology, 2018)
Feedback has two main components. One is valence that indicates the wrong or correct behavior, and the other is the informative value that refers to what we can learn from feedback. Aimed to explore the neural distinction of these two components, we provided participants with a segmented Wisconsin Card Sorting Task, in which they received either positive or negative feedback at different steps. The informative value was manipulated in terms of the order of feedback presentation. The results of event-related potentials time-locked to the feedback presentation confirmed that valence of feedback was processed in a broad epoch, especially in the time window of feedback-related negativity (FRN), reflecting detection of correct or wrong card sorting behavior. In contrast, the informative value of positive and negative feedback was mainly processed in the P300, possibly reflecting information updating or hypothesis revision. These findings provide new evidence that informative values of feedback are processed by cognitive systems that differ from those of feedback valence.